TERROIR ON TRIAL: THE LEGAL IMPLICATIONS OF CLIMATE CHANGE ON THE VALIDITY OF GEOGRAPHICAL INDICATIONS - Debrina Rahmawati; Yekti Sri Rahayu (Faculty of Law, Widya Gama University, Malang, 2026)
Climate change poses a fundamental challenge to the legal framework of Geographical Indications (GIs) in Indonesia, which is traditionally grounded in the assumption of terroir stability. This article examines (1) the legal validity, infringement, and potential revocation of GIs under the Indonesian Geographical Indications Law when climate change alters or undermines the environmental conditions underlying registered GIs, and (2) proposes legal adaptation strategies for the future governance of Indonesian GIs in response to climate change. This study employs a normative juridical research design using statutory and comparative law approaches. The findings indicate that (1) the current legal framework governing the validity, infringement, and revocation of GIs exhibits a deficit in the rule of recognition, as conceptualized in Hart’s legal theory, particularly in addressing environmental transformations caused by climate change; and (2) legal adaptation to climate change may be advanced by incorporating several regulatory elements from the French GI regime, including (a) provisions enabling the revision of product specifications, (b) recognition of the GI management organization (Masyarakat Perlindungan Indikasi Geografis / MPIG) as a public-interest actor, and (c) the expansion of the dialogical authority of the Directorate General of Intellectual Property (DJKI).